Facebook live como herramienta alternativa para la difusión de contenidos radiofónicos: el caso de “Pujilí y sus realidades” en la radio el sol de Pujilí. - Núñez Escobar, Erika Aracelly (2018)
Facebook Live is an alternative tool for broadcasting radio content that has allowed radio to enter the new digital ecosystem. And to the prosumer paradigm that refers to the audience that produces and consumes information. However, it is necessary to understand what types of content should be built for these new audiences and new content distribution platforms. Therefore, the general objective of the research is to evaluate the scope that Facebook Live has as an alternative tool for the diffusion of radio content: for this reason "Pujilí y sus Realidades" on El Sol de Pujilí radio. The methodology used for data collection is of a qualitative and quantitative nature through the application of research techniques such as the survey, the interview and the observation file. Finally, it is concluded that although the use of digital platforms is applied, there is a lack of knowledge about the management of strategies and contents that enhance the interaction of the prosumer in hypermedia